Agama Hindu dan Budaya Bali: Warisan Luhur dalam Kehidupan Modern - Subawa, Ida Bagus Gede (Kamaya: Jurnal Ilmu Agama, 2024)
Religion, previously regarded as a shared source of values and social norms, is now increasingly understood as a personal reconstruction process reflecting individual freedom in interpreting religious teachings. In Bali, this phenomenon is evident in the evolving practices of Balinese Hinduism, influenced by modernization and globalization. Nevertheless, the Balinese Hindu identity remains preserved by most of the community as an integral part of their culture. Balinese Hinduism plays a crucial role in maintaining social and cultural harmony through the implementation of panca yadnya rituals and the Tri Hita Karana principles, which emphasize balance in relationships between humans, God, and nature. This study aims to examine the dynamics of changes in Balinese Hindu practices and explore their role in maintaining social and cultural harmony amidst the challenges of globalization. The method employed is a literature review, analyzing relevant academic sources to develop theoretical contributions toward the preservation of Balinese Hindu culture and religion. The findings reveal that despite the increasing influence of modernization, local religious practices such as panca yadnya remain central to Balinese life. The tri hita karana principles continue to serve as a foundational framework supporting cultural sustainability and social harmony in the face of changing times. In conclusion, the Balinese Hindu identity demonstrates significant resilience through the integration of local traditions with modern challenges. This study highlights the importance of preserving Balinese Hindu religion and culture as a means of safeguarding social harmony and local wisdom in the era of globalization.